Worcester Guidlhall - White, Thomas
The work of another of When's pupils, Thomas White (1674-1748), who built the stone-and-brick building with its statues of Charles I, Charles II and Queen Anne. The parallel with early Tudor works is evident. Such statues set in niches are a part of the principal elevations of Montacute House built in 1588, and of Thomas Holt's work at Oxford from 1610-1620.